2008
DOI: 10.1177/0269881108091584
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the effects of the antioxidant Pycnogenol® on cognitive performance, serum lipid profile, endocrinological and oxidative stress biomarkers in an elderly population

Abstract: The study examines the effects of the antioxidant flavonoid Pycnogenol on a range of cognitive and biochemical measures in healthy elderly individuals. The study used a double-blind, placebo-controlled, matched-pair design, with 101 elderly participants (60-85 years) consuming a daily dose of 150 mg of Pycnogenol for a three-month treatment period. Participants were assessed at baseline, then at 1, 2, and 3 months of the treatment. The control (placebo) and Pycnogenol groups were matched by age, sex, body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 47 publications
9
129
2
Order By: Relevance
“…30 A human clinical study reported that elderly individuals tolerated 150 mg/day of PYC for 3 months without any significant side effects. 31 PYC has very low acute and chronic toxicity with mild unwanted effects occurring in a small percentage of human subjects. 32 The beneficial effects of PYC 24 indicate it can cross a compromised blood-brain barrier, which is breached soon after injury.…”
Section: Ansari Et Al Discussionmentioning
confidence: 99%
“…30 A human clinical study reported that elderly individuals tolerated 150 mg/day of PYC for 3 months without any significant side effects. 31 PYC has very low acute and chronic toxicity with mild unwanted effects occurring in a small percentage of human subjects. 32 The beneficial effects of PYC 24 indicate it can cross a compromised blood-brain barrier, which is breached soon after injury.…”
Section: Ansari Et Al Discussionmentioning
confidence: 99%
“…The eight visuospatial measures, used in eleven different studies, showed significant effects in four studies, with respect to flavonoid treatments (20,90,91) and Zn (80) , although Santos et al (91) (n 48) and Gleason et al (20) (n 30) had relatively small sample sizes, and the randomisation process adopted by Santos et al (91) may not have been reliable as they reported baseline differences in IQ between groups.…”
Section: Working Memorymentioning
confidence: 99%
“…Spatial Working Memory Task (CDR) (90) Positive: flavonoid (90) (28,72,75,79,92) Positive: B vitamins (79) Positive: flavonoid (92) Y Y Y Memory: episodic -verbal Short Story Recall (WMS) (19,21,22) Positive: flavonoid (19,21) (29,68,70,71,77,83,90,91) Positive: B vitamins (77) Positive: multivitamins/ multiminerals Positive: B vitamins (75) Negative: B vitamins (73) Positive: flavonoid (84,91,92) Y Y Y Psychomotor: processing speed Finger-Tapping Task (24,71,89) -Y Y Psychomotor: processing speed Grooved Pegboard (20,25) Positive flavonoid (20) Y Y Psychomotor: processing speed Identical Forms Task (78) Positive: B vitamins (78) The working memory span task (the Digit Span Backward test) showed significant effects in only two of eight studies, for flavonoids (84,92) , although as mentioned earlier, it is difficult to judge the quality of these results due to the lack of statistical rigour to which the data were subjected, and/or to lack of information provided.…”
Section: Working Memory: Visual/ Visuospatialmentioning
confidence: 99%
See 2 more Smart Citations